The Power of Product Recommendation Networks - Kane, Gerald; Oestreicher-Singer, Gal; Sundararajan, Arun (MIT Sloan Management Review, 2017)
Much as relationships in social networks have been analyzed to understand and influence how ideas flow among people, researchers wondered whether it might be possible to use the structure of product recommendation networks online to understand or influence how demand flows among products. The short answer is yes, and the implications for marketers are important.
Keywords: Product management; Product differentiation; New products; Produits commerciaux; Gestion; Produits commerciaux; Différenciation